Consequences of colectomy: pathogenetic damages and correction outlooks - S. R. Bashirov (Бюллетень сибирской медицины)
On the base of experimental and clinical investigations there has been found that continent reservoir ileorectostomies after colectomy under the rectal contents effect had been exposed to degenerative and dysplastic mucous changes. These damages prohibit from stool formation and increase the risk of reservoir malignization. A method of continent reservoir ileorectostomy formation with restraining and areflux mechanism has been developed for pathological transformation of ileal structure. Results of morphological and instrumental investigation methods made on 33 dogs and 6 patients after colectomy show that the restraining and areflux mechanism permits to avoid displastic and degenerative changes in ileal reservoir mucous coat and to recover the stool formation due to motor-evacuation function regulation and keeping the constant physical, chemical and bacterial reservoir and rectum properties after colectomy.